200k views
15 votes
Simplify the expression -6 - 7 (c+10)

User Acanimal
by
5.1k points

1 Answer

9 votes

Answer:


-6-7\left(c+10\right)=-7c-76

Explanation:

Given the expression


-6\:-\:7\:\left(c+10\right)

simplifying the expression


-6-7\left(c+10\right)

Expanding -7(c + 10) = -7c - 70


-6\:-\:7\:\left(c+10\right)=-6-7c-70

subtract the numbers: -6 - 70 = -76


=-7c-76

Therefore, we conclude that:


-6-7\left(c+10\right)=-7c-76

User Gambit
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.